Approved revenue, recurrent and capital estimates of the government of Kebbi State of Nigeria. - Nigeria; Nigeria (Lagos : Federal Govt. Press, 1983)
The proposals for the state's 1992 fiscal year for our deliberations and approval.
aia 12/02/2019
Loans
Keywords: Budget; Revenue; Öffentlicher Haushalt; Nigeria; Budget; Expenditures, Public; Revenue; Nigeria; Nigeria